Determination of Osteoporosis Risk in Post-Menopausal Women Using the Malaysian Osteoporosis Screening Tool: A Pilot Study in a Community Pharmacy - Athirah Ahmad Latif; Nursyuhadah Othman; Saliha Azlan; Nik Ateerah Rasheeda Mohd Rocky; Siti Sarah Syahirah Kushairi; Nik Aisyah Najwa Nik Mustaffa Shapri; Mohd Shahezwan Abd Wahab (Borneo Journal of Pharmacy, 2026)
Osteoporosis detection remains suboptimal in Malaysia. This study aimed to evaluate osteoporosis risk using the Malaysian Osteoporosis Screening Tool (MOST) and supplementation behaviors in a community pharmacy. A cross-sectional study was conducted in a private pharmacy in Temerloh, Pahang (May–August 2025). Postmenopausal women (n = 126) completed questionnaires and underwent anthropometric assessment (BMI, hip circumference). MOST scores were calculated, and group differences were analyzed using Mann–Whitney U and Kruskal–Wallis tests (p <0.05). All participants were classified as "at risk" (MOST >4); the median score was 42.0 (IQR 12.0–42.0). Scores were significantly higher among women aged >60 years (p <0.001), those with lower education (p = 0.005), and the unemployed (p = 0.005), but were unrelated to income, ethnicity, or residence. Hip circumference was >90 cm in 96.8% of cases, limiting its discriminatory value. Lifestyle and clinical factors, including family history, hormone therapy, steroid use, smoking, coffee intake, carbonated drinks, and calcium- and vitamin D-rich foods, were not associated with MOST scores. Supplement use included calcium (27.8%), vitamin D (35.7%), and combined calcium–vitamin D (26.2%). Calcium users had higher scores (p = 0.011); vitamin D or combined use showed no differences (p >0.05). MOST concentrated nearly all postmenopausal women into the high-risk category, primarily reflecting age and menopausal duration. Findings support its feasibility in community pharmacies and highlight gaps in coordinated calcium and vitamin D supplementation.